Efficient Access to 2‐Pyrones via Carbene‐Catalyzed Oxidative [3+3] Reactions between Enals and Nitrogen Ylides. Issue 7 (9th May 2019) - Zheng, Pengcheng; Li, Chengcheng; Mou, Chengli; Pan, Dingwu; Wu, Shuquan; Xue, Wei; Jin, Zhichao; Chi, Yonggui Robin
Abstract: Pyrones are important structural units in natural products and synthetic functional molecules. Here, we report a carbene‐catalyzed oxidative [3+3] cycloaddition reaction between enals and nitrogen ylides for quick access to 2‐pyrones. Inexpensive and easily prepared 2′‐pyridinium acetophenone bromide salts are used as precursors of pyridinium ylides to react with enals in our catalytic reactions. Abstract : 3 vs 3 : A carbene‐catalyzed oxidative [3+3] cycloaddition reaction between enals and nitrogen ylides for quick access to 2‐pyrones is reported. Inexpensive and easily prepared 2′‐pyridinium acetophenone bromide salts are used as precursors of pyridinium ylides to react with enals.